Multi-modal mechanophores based on cinnamate dimers. Issue 1 (December 2017) - Zhang, Huan; Li, Xun; Lin, Yangju; Gao, Fei; Tang, Zhen; Su, Peifeng; Zhang, Wenke; Xu, Yuanze; Weng, Wengui; Boulatov, Roman
Abstract Mechanochemistry offers exciting opportunities for molecular-level engineering of stress-responsive properties of polymers. Reactive sites, sometimes called mechanophores, have been reported to increase the material toughness, to make the material mechanochromic or optically healable. Here we show that macrocyclic cinnamate dimers combine these productive stress-responsive modes. The highly thermally stable dimers dissociate on the sub-second timescale when subject to a stretching force of 1–2 nN (depending on isomer). Stretching a polymer of the dimers above this force more than doubles its contour length and increases the strain energy that the chain absorbs before fragmenting by at least 600 kcal per mole of monomer. The dissociation produces a chromophore and dimers are reformed upon irradiation, thus allowing optical healing of mechanically degraded parts of the material. The mechanochemical kinetics, single-chain extensibility, toughness and potentially optical properties of the dissociation products are tunable by synthetic modifications. Mechanochemistry offers exciting opportunities for molecular engineering of stress-responsive properties of polymers. Here the authors show that macrocyclic cinnamate dimers in a polymer chain can undergo dissociation on the sub-second timescale under 1–2 nN stretching to yield a chromophore that then can be optically healed.